The Mystery of the Titanic : What Really Happened - Dieckmann, Caitlyn (URJ-UCCS: Undergraduate Research Journal at UCCS, 2020)
Buried in the depths of the ocean lies a magnificent structure, surviving only as a ghost from the past. The RMS Titanic lies across miles of seafloor as a result of the events leading up to, and on the night of, April 14, 1912, when the ship liner struck an iceberg and slowly began its descent into the Atlantic ocean forever (History.com Editors, 2009). The evidence of the accident still lies with the shipwreck today. Many historians throughout the years have speculated what really happened on that moonless night, many years ago, providing several answers still prominent to this day. The shipwreck was the result of a flaw when the ship was built, competition between another ship building company and White Star Line, and the natural circumstances of the night being almost too perfect for smooth sailing. These factors led to this tragic moment in history, allowing history the ability to learn whether or not more deaths could have been avoided, see from the perspective of the survivors, and understand what the wreck still means to the modern day.